The Meaning of Land Acquisition Compensation and its Utilization Strategy in Affected Communities in the Pejagan-Pemalang Toll Road Construction. - Fatimah, Nurul; Hutami, Edwina Renaganis (Komunitas, 2020)
The process of negotiation and compensation in land acquisition is often accompanied by dramatic actions between the community and the management and the government. However, this phenomenon did not arise in the case of land acquisition that occurred in the construction of the Pejagan-Pemalang toll road. The purpose of this study is to uncover and thoroughly describe how people interpret the compensation payments for the land they receive and how they use the compensation for their lives. Qualitatively the research data was collected through interviews, observations, FGDs and documentation, aimed at several informants both the affected communities and the project management of the toll road. Henceforth the data will be analyzed interactively by paying attention to the validity of the data using triangulation. The results showed there was a shift in the meaning of compensation money in the Kalimati village community from "ganti rugi" changed to "ganti untung". Whereas the strategy in utilizing the compensation money is patterned accumulation, consolidation and survival based on rational, instrumental, affective and value-oriented actions.